Fungal mash enzymatic pretreatment combined with pH adjusting approach facilitates volatile fatty acids yield via a short-term anaerobic fermentation of food waste. (September 2022) - Zhang, Mingjiang; Zhang, Dejin; Wei, Yidan; Zhou, Bo; Yan, Cheng; Wang, Dianzhan; Liang, Jianru; Zhou, Lixiang
Graphical abstract: Highlights: The concentration of COD increased by 116.9% after the enzymatic pretreatment of CA. Adding CA improves the solubility and the degradability of the organic substance. pH adjusting facilitated the conversion of polysaccharides and proteins to VFAs. The combination VFAs production was 32.0 g COD/L, 10 times higher than the control. pH adjusting altered the main metabolic pathway from lactate-type to butyrate-type. Abstract: As an alternative for commercial enzyme, crude enzyme of fungal mash could promote food waste (FW) hydrolysis, but its specific effects coupled pH adjusting on the production of volatile fatty acids (VFAs) remains unknown. The crude enzyme produced from an Aspergillus awamori, named complex-amylase (CA), was added to short-term anaerobic system of FW fermentation. Results showed that adding CA significantly improved the solubility and degradability of biodegradable and non-biodegradable organics in FW, where the SCOD concentration with adding CA increased by 116.9% relative to the control but a marginal enhancement on VFAs yield. In contrast, adding CA combined with adjusting pH 8 markedly increased the VFAs production to 32.0 g COD/L, almost 10 times as much as the control. Besides, pH adjusting altered the metabolic pathway from lactate-type to butyrate-type. Adding CA coupled pH adjusting significant increase the component of butyrate compared with pH adjusting alone. Moreover, microbial community analysis indicated that adding CA reinforced proportion of the butyrate-producing bacteria (e.g., Dialister ) under basic conditions, thus enhancing the butyrate metabolic pathways. This study demonstrated that fungal mash pretreatment coupled pH conditioning could be an economical way to enhance VFAs yield for FW valorization during anaerobic fermentation.